[the] Sensorium of Machine Architecture and the Onomatope/o - Cantley, Bryan (Architecture Image Studies, 2020)
This paper proposes an association between Cantley’s use of a machine architecture and his experimental drawing, as well as explores the emerging relationships between media [an/notation] and the[ir] residual architectural dialogue. There is an inherent rapport found between the Connotation, Notation, and Annotation found within the/his architectural drawing. This connective tissue becomes the fodder for a new site for architectural speculation. The palimpsest and pentimento both become the notation and annotation in a new set of investigational works. It additionally briefly traces a synthetic structure of a con-structed language to describe the fuzzy parameters of these constructs.